In search of copassion: Creating a novel concept to promote re-enchantment at work - Anne Birgitta Pessi; Anna Martta Seppänen; Jenni Spännäri; Henrietta Grönlund; Frank Martela; Miia Paakkanen (BRQ Business Research Quarterly, 2022)
Re-enchantment taps well into the current zeitgeist: The rising focus on emotions and post-material values also in organizational context. Enchantment is deeply tied to socially generated emotions. Our aim is to develop the concept of copassion, referring to the process of responding to the positive emotion of a fellow human being. Concepts are crucial as they shape our understanding of the world. Our core claim is relating to our colleagues' positive emotions not only enables and maintains but also fosters enchantment at work. In this article, by laying the ground by discussing enchantment and the theoretical framework of intersubjectivity, we will link copassion to the physiological and evolutionary basis of humans, as well as explore its conceptual neighbors. Finally, we will discuss intersubjectivity, and particularly mutual recognition, as well as the inseparability of compassion and copassion in human experience at work, and its implications to the study of enchantment
Keywords: M14; 650; business ethics; compassion; copassion; corporate social responsibility; Enchantment; re-enchantment; workplaces